A proposed human resource management model for zakat institutions in Malaysia. Issue 1 (17th June 2019) - Hasan, Aznan; Hassan, Rusni; Engku Ali, Engku Rabiah Adawiah; Engku Ali, Engku Muhammad Tajuddin; Abduh, Muhamad; Noordin, Nazrul Hazizi
Abstract : Purpose: The purpose of this study is to propose a contemporary human resource management (HRM) framework by zakat institutions, which collect and manage religious alms, both obligatory (zakat) and voluntary ( ṣadaqah ), in Malaysia. Design/methodology/approach: In doing so, discussions pertaining to the key elements of zakat institutions' HRM including recruitment, selection, performance appraisal, training and development and compensation are gathered from the existing literature and other sources of information such as zakat institutions' websites and publications. In addition, zakat officers' insight on how HRM is practiced at their institutions is gathered through a series of semi-structured interviews and incorporated in the findings of this study. Findings: The paper finds that the state government, by virtue of the State Islamic Religious Council (SIRC), which is the sole trustee of all waqf properties in Malaysia, may have significant influence in formulating the human resource strategies and policies in zakat institutions. Research limitations/implications: The proposed HRM model can be a useful reference for SIRC in enhancing the current human resource practice in its respective zakat institutions. Originality/value: The novelty of this study lies in the proposed HRM model applicable to zakat institutions. The model emphasizes the alignment between the zakat institutions' HRM practice and their zakat collection and distribution goals, as well as zakat management objectives in general.